The possible role of ammonia in phototaxis of migrating slugs of Dictyostelium discoideum - Bonner, J. T. (1988)
Previously we showed that the rising cell masses of cellular slime molds orient away from high concentrations of ammonia gas, presumably by speeding up the cells on one side. Here we show that in the same way NH(3) could also be involved in the highly sensitive phototaxis found in the migrating slugs of Dictyostelium discoideum. We have evidence that light increases their speed of migration and their production of NH(3). Since unilateral light is concentrated on the distal side of a cell mass by the “lens effect,” this leads to the obvious hypothesis that the light stimulates the local production of NH(3), which, in turn, stimulates the cells in the illuminated region to move faster.